PACAP immunoreactivity in the rat superior cervical ganglion in comparison to VIP - Klimaschewski, Lars Peter; Mauser, Cornelia; Heym, Christine (Neuroreport, 1996)
THE presence and regulation of pituitary adenylate cyclase activating peptide (PACAP) was investigated in the adult rat superior cervical ganglion. Double-labelling immunofluorescence using specific antibodies against PACAP and vasoactive intestinal peptide (VIP) revealed a dense innervation of postganglionic sympathetic neurones by PACAP-immunoreactive but VIP-negative nerve endings that mainly were of preganglionic origin since they disappeared after transection of the cervical sympathetic trunk. Since PACAP regulates transmitter synthesis and release in sympathetic neurones in vitro, this finding provides a morphological correlate for modulatory effects of PACAP in vivo. Few neurones contained PACAP under normal conditions. However, the number of PACAP-positive neurones increased in response to axotomy of the postganglionic nerves. Many of the newly PACAP-positive neurones also contained VIP, suggesting that both peptides are regulated by similar mechanisms.
Gesehen am 06.11.2025